Efektivitas Formasi Tempat Duduk Tipe U dan Chevron terhadap Hasil Belajar Peserta Didik - Novy Kusuma Wardani; Darlen Sikumbang; Rini Rita T Marpaung (Universitas Lampung, 2019)
This study aimed to determine the effectiveness of U, chevron and theater seating formation on student learning outcomes in the subject matter of the plant tissues in Senior High School 3 Metro. The population was XI grade science students and samples were XI science 1, XI science 2, and XI science 3 grade’s students which were selected by purposive sampling technique. The design of this study was a non-equivalent pretest-posttest. Measurement of effectiveness on cognitive aspects based on differences in N-gain, while the calculation of affective and psychomotor aspects based on the interpretation of Qualitative Achievement Index and score improvement calculation. The results showed that the average N-gain value, affective and psychomotoric aspects of the experimental class I was higher than the experimental class II and control class. In conclusion, there were differences in the effectiveness of the three seating formations that are determined against learning outcomes and the U was the most effective then chevron and theater formations.Penelitian ini bertujuan mengetahui efektivitas formasi tempat duduk tipe U dan Chevron terhadap hasil belajar peserta didik pada materi pokok jaringan tumbuhan di SMAN 3 Metro. Populasi penelitian ini adalah seluruh peserta didik kelas XI IPA dan sampelnya adalah peserta didik kelas XI IPA 1, XI IPA 2, dan XI IPA 3 yang diambil dengan teknik purposive sampling. Desain penelitian ini adalah pretes-postes non ekuivalen. Pengukuran efektivitas pada aspek kognitif berdasarkan perbedaan N-gain, sedangkan perhitungan aspek afektif dan psikomotorik berdasarkan tafsir indeks prestasi kualitatif. Hasilnya menunjukkan bahwa peserta didik kelas eksperimen I memiliki N-gain kognitif dan peningkatan nilai aspek afektif dan psikomotorik tertinggi daripada peserta didik kelas eksperimen II dan kelas kontrol. Kesimpulannya, terdapat perbedaan efektivitas dari ketiga formasi tempat duduk dengan formasi U yang paling efektif daripada formasi chevron dan teater.Kata kunci : efektivitas, formasi tempat duduk, hasil belajar